Didactic models for active and inquiry-based learning of machines and mechanisms - Bartolomé, E (International journal of mechanical engineering education, 2025)
Didactic models are invaluable resources for teaching Machines and Mechanisms, a crucial subject in the Engineering curriculum. This work investigates the impact of various types of models on learning outcomes across different instructional approaches, from traditional to active and inquiry-based learning methods. We analyzed a range of didactic models used in a second-year Theory of Machines and Mechanism (TMM) course at EUSS School of Engineering in Barcelona over the past decade, including: i) mechanical models built with “Meccano” parts, 3D-printed models, and kits simulating “fairground attractions”, introduced in traditional teaching settings; ii) real machines and student-developed models used in in TMM courses based on the “Study and Research Path” (SRP) approach, and iii) advanced didactic machines, created by fourth-year students. We discuss the educational benefits provided by these models, considering aspects like the theoretical concepts they mobilize, their construction (by teachers or students), design flexibility, materials used, complexity, and realism. Additionally, we examine how these models enrich the Media and Milieu dialectics, promote the development of both technical and transversal skills, and present a range of advantages and challenges in each TMM context. Our findings offer valuable insights into how models enhance the teaching and learning experience in Machines and Mechanisms, guiding instructors in selecting appropriate models and instructional strategies based on course objectives, student characteristics, and contextual constraints.